Plasticized polymer blend electrolyte based on chitosan for energy storage application: structural, circuit modeling, morphological and electrochemical properties - M. H., Hamsan; Nofal, Muaffaq M.; Aziz, Shujahadeen B.; Brza, M. A.; Dannoun, Elham M. A.; Murad, Ary R.; M. F. Z., Kadir; Saifful Kamaluddin, Muzakir (MDPI, 2021)
Chitosan (CS)-dextran (DN) biopolymer electrolytes doped with ammonium iodide (NH4I) and plasticized with glycerol (GL), then dispersed with Zn(II)-metal complex were fabricated for energy device application. The CS:DN:NH4I:Zn(II)-complex was plasticized with various amounts of GL and the impact of used metal complex and GL on the properties of the formed electrolyte were investigated.The electrochemical impedance spectroscopy (EIS) measurements have shown that the highest conductivity for the plasticized system was 3.44 × 10−4 S/cm. From the x-ray diffraction (XRD) measurements, the plasticized electrolyte with minimum degree of crystallinity has shown the maximum conductivity. The effect of (GL) plasticizer on the film morphology was studied using FESEM. It has been confirmed via transference number analysis (TNM) that the transport mechanism in the prepared electrolyte is predominantly ionic in nature with a high transference number of ion (ti)of 0.983. From a linear sweep voltammetry (LSV) study, the electrolyte was found to be electrochemically constant as the voltage sweeps linearly up to 1.25 V. The cyclic voltammetry (CV) curve covered most of the area of the current–potential plot with no redox peaks and the sweep rate was found to be affecting the capacitance. The electric double-layer capacitor (EDLC) has shown a great performance of specific capacitance (108.3 F/g), ESR(47.8 ohm), energy density (12.2 W/kg) and power density (1743.4 W/kg) for complete 100 cycles at a current density of 0.5 mA cm−2.